"Deixem que eu fale por mim": autoficção na crônica de João Ubaldo Ribeiro - Gonçalves, Débora da Silva Chaves (2020)
Based on the chronicles of João Ubaldo Ribeiro, we intend to identify the presence of self-fiction (Doubrovsky, 1977) and the consequent problematization of identities, memories and experiences through personal writing, considering small memories described in light texts, based on the absence experienced by subject of experience. This form of negotiation between theories is capable of betraying and confusing the reader, by ensuring the right to an unpretentious text, but which at the same time becomes intimate and personal for the one who constructs it. Thus, the trajectory experienced by the chronicler, which runs through history and the memory reinvented in his narrative, offers the necessary transit to understand the exchange with his faithful reader and the desire for and “eternal return” to a fictionalized Bahia, within a Itaparica island forged in the imagination of João Ubaldo Ribeiro and configured in his memory. With this, there is an identification with his mother-mother that was never left aside and is recovered through self-fiction and textual record.